Fault detection method using truth table in quantum circuits - Yılmaz, Reyhan; Şanlı, Tuba; Yaman, Orhan; Karaköse, Mehmet (My University, 2023)
Quantum circuits are the foundation of quantum computers and quantum technologies. These circuits are created using quantum systems called quantum bits (qubits). Qubits are in a complex state that can take both a 0 and a 1 state at the same time, unlike the bits used by traditional computers. This provides features such as the ability of quantum circuits to perform parallel processing and solve some computational problems faster. There are many types of faults in quantum circuits. It is important to detect faults so that the quantum circuits to be developed can produce accurate results. In this study, a method using a truth table is proposed to detect possible faults that may occur in quantum circuits. The truth table is obtained from the '.tfc' files used in the creation of quantum circuits. The obtained truth table is compared with the output of the quantum circuit.
Bildiri - Yayımlanmış
Keywords: Quantum circuits; Fault detection; Quantum computing; Truth table